Associations between Social-Media Usage Patterns and Semester CGPA: A Cross-Sectional Study of University of Dhaka Undergraduates - Mamun Moon, Montasir; Umme Anisha, Mahmuda (South Asian Journal of Social Sciences and Humanities, 2025)
The widespread adoption of social media has significantly reshaped students’ daily lives,  particularly in the realm of education. As digital connectivity becomes more embedded in  academic routines, understanding its actual impact on student performance has become crucial.  While global research has documented both positive and negative associations between social media usage and academic outcomes, evidence from Bangladesh remains scarce. This study  addresses that gap by examining how usage patterns-categorized by purpose (education,  entertainment, communication) and duration-relate to semester CGPA among undergraduates  at the University of Dhaka. A cross-sectional quantitative survey was conducted using online  data collected from 100 students. Statistical analyses, including correlation and multiple  regression, were applied to explore associations. The results revealed a strong negative  correlation between total weekly usage time and CGPA, indicating that longer time spent on  social media generally predicts lower CGPA. However, when social media is used for  educational purposes, it shows a moderate and statistically significant positive relationship with  semester CGPA. Entertainment-driven usage exhibited a strong negative effect, while  communication-related usage showed a weak but positive correlation. Multiple regression  confirmed that time spent, educational use, and entertainment use are significant predictors of  CGPA, explaining 49,3% of the variation in academic performance. Educational purpose  emerged as the only positive predictor among the three, while communication use was not  significant in the multivariate model. These findings suggest that social media's impact is not  inherently negative or positive but depends on how and why it is used. Students, educators, and  policymakers should focus on promoting purposeful and educational use while minimizing  distractions linked to entertainment overuse. As the data were drawn from a single institution  using convenience sampling, generalizability is limited. Nonetheless, this research provides  valuable insights into optimizing digital behavior to support academic success within the  Bangladeshi context.
Keywords: Social media usage patterns; academic results; educational technology; student engagement